Omission of Postoperative Radiotherapy in Women Aged 65 Years or Older With Tubular Carcinoma of the Breast After Breast-Conserving Surgery - Wu, San-Gang; Zhang, Wen-Wen; Sun, Jia-Yuan; Li, Feng-Yan; Chen, Yong-Xiong; He, Zhen-Yu (Frontiers in Oncology, 2018)
Introduction: To investigate the temporal trends of postoperative radiotherapy (RT) administration and the effects of omitting postoperative radiotherapy (RT) on breast cancer-specific survival (BCSS) in women aged ≥65 years with tubular carcinoma (TC) of the breast who received breast-conserving surgery (BCS). Methods: We included women aged ≥65 years with non-metastatic TC of the breast who underwent BCS between 2000 and 2013 using the Surveillance, Epidemiology and End Results database. Statistical analyses were performed using chi-square tests, Kaplan-Meier analyses, Cox proportional hazards models, and a 1:1 propensity score-matching (PSM). Results: Before PSM, a total of 1475 patients with tumor size ≤2cm, node-negative disease, and estrogen receptor positive disease were identified, including 927 (62.8%) underwent postoperative RT and 548 (37.2%) had postoperative omission of RT. The administration of postoperative RT steadily declined over the study period. Patients with younger age, larger tumor size, and other race/ethnicity were more likely to receive postoperative RT. The median follow-up duration was 85.0 months, the 5- and 10-year BCSS rates were 98.7% and 97.9%, respectively. The median BCSS was 161.9 and 165.0 months for patients with and without postoperative RT, respectively, and the corresponding 5-year BCSS rates were 98.5% and 98.8%, respectively (p = 0.134). Prognostic analysis indicated that postoperative RT was not associated with improved BCSS rates compared to RT omission (p = 0.134). After PSM, a total of 431 completely-matched pairs were generated. In the matched population, the 5-year BCSS rates were 98.6% and 98.4% in non-postoperative RT and postoperative RT groups, respectively (p = 0.858). The univariate analyses also confirmed that the administration of postoperative RT was not associated with better BCSS (p = 0.858). Conclusions: The incidence of breast cancer-related death is probably sufficiently low to avoid postoperative RT in women aged ≥65 years with TC of the breast after BCS.